2019
DOI: 10.1002/term.2799
|View full text |Cite
|
Sign up to set email alerts
|

Promising effects of exosomes isolated from menstrual blood‐derived mesenchymal stem cell on wound‐healing process in diabetic mouse model

Abstract: Wound healing is a complicated process that contains a number of overlapping and consecutive phases, disruption in each of which can cause chronic nonhealing wounds. In the current study, we investigated the effects of exosomes as paracrine factors released from menstrual blood-derived mesenchymal stem cells (MenSCs) on wound-healing process in diabetic mice. The exosomes were isolated from MenSCs conditioned media using ultracentrifugation and were characterized by scanning electron microscope and western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 75 publications
5
162
0
Order By: Relevance
“…On the other hand, they reported that the EV inhibited the biosynthesis of the a-SMA protein . Those results are in agreement with the ones reported by other authors Dalirfardouei et al, 2019). Therefore, the EV derived from the MSC of adipose tissue reduced scar formation, due to their effects on fibroblasts.…”
Section: Fibroblastssupporting
confidence: 94%
“…On the other hand, they reported that the EV inhibited the biosynthesis of the a-SMA protein . Those results are in agreement with the ones reported by other authors Dalirfardouei et al, 2019). Therefore, the EV derived from the MSC of adipose tissue reduced scar formation, due to their effects on fibroblasts.…”
Section: Fibroblastssupporting
confidence: 94%
“…Results show that Alg hydrogel containing EXO considerably improved wound closure, collagen synthesis, and vessel formation at wound area compared with Alg hydrogel and sterile gauze as control groups. Previous studies have demonstrated that the EXO transplantation can elicit almost the same healing outcomes as compared to whole‐cell transplantation (Dalirfardouei, Jamialahmadi, Jafarian, & Mahdipour, ). Therefore, we hypothesized whether an appropriate delivering system in the wound area could overcome the disadvantages and risks coupled with whole‐cell therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In a rat model of diabetes, MenSC-derived EVs were tracked in, and enhanced the number of pancreatic β cell islets and raised serum insulin, without impact on non-fasting blood glucose ( Mahdipour et al, 2019 ). MenSC-derived exosomes impacted wound healing in a mouse model of diabetes through M2 macrophage polarization, induction of neoangiogenesis and re-epithelialization ( Dalirfardouei et al, 2019 ).…”
Section: Therapeutic Potential Of Emsc and Menscmentioning
confidence: 99%